Room temperature continuous wave perovskite laser based on chiral amine ligand and preparation method thereof
The high-quality quasi-two-dimensional perovskite film was prepared by a solution method based on chiral amine ligand, which solved the problem of uneven phase distribution in perovskites, achieved low laser threshold and high energy transfer efficiency, and prepared excellent performance Perovskite lasers are suitable for a variety of light sources and optoelectronic integration fields.
Patent Information
- Application Number
- CN202411804143.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-12-10
AI Technical Summary
There is a problem of uneven phase distribution in quasi-two-dimensional perovskites, which leads to disordered states in space and energy, increases radiation-free composite channels, reduces energy transfer efficiency, and makes it difficult to form a standard four-level structure, affecting the exit of lasers.
High-quality quasi-two-dimensional perovskite films are prepared by solution method based on chiral amine ligands, and uniform gain medium and spacer layer are formed by spin coating. Combined with high-quality optical microcavities, the perovskite defect density is reduced and current-carrying is enhanced. Sub-pumping efficiency suppresses electroacoustic coupling effect.
Achieve excellent four-level material structure, low laser threshold, high energy transfer efficiency, and enhance particle number inversion and stimulated radiation amplification. The prepared perovskite laser has low threshold, good time and space coherence, which is suitable for Various light sources and optoelectronic integration fields.
Smart Images

Figure CN119297742A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optoelectronic devices, and in particular to a room temperature continuous wave perovskite laser based on a chiral amine ligand and a preparation method thereof. Background Art
[0002] In the post-Moore era, micro-nano integrated photonic devices have become an indispensable core component in the process of information operation and transmission. With the increasing demand for integration, traditional electronic devices face multiple bottlenecks, such as response speed, energy consumption, modulation and bandwidth. Due to the advantages of ultra-high-speed propagation, low loss and diversified modulation methods of photons, photonic-based circuits have the potential to overcome these limitations and enhance the functions of electronic devices. Macroscopic free light paths (optical paths) have demonstrated capabilities in transmission and logic operations, including waveguide propagation, directional beam splitting, intensity modulation and phase modulation. However, it is still a challenge to manufacture highly integrated large-scale photonic circuits. Therefore, on-chip integrated photonic devices and circuits have become an ideal solution and have received widespread attention. Although the research on silicon-based integrated photonic devices has made significant progress, efficient and low-cost heterogeneous integration based on group IV and group III-V coherent light sources remains a difficult problem. Therefore, active integrated photonic circuits using new gain materials are crucial to future research in integrated photonics. In the past decade, an emerging class of direct bandgap semiconductor materials, metal halide perovskites, have attracted widespread attention due to their high gain coefficients, low defect state concentrations, wide wavelength tuning, and ease of silicon photonic integration. In addition, single-crystalline perovskite microstructures with regular and special morphologies have demonstrated excellent laser and waveguide properties. Given these advantages, perovskite semiconductors are considered to be a promising platform for realizing micro-nano light sources and photonic devices at room temperature. In traditional lasers, the generation of lasers must meet the following three basic conditions: population inversion, threshold phenomenon, and optical feedback. Population inversion means that the number of particles at higher energy levels must be greater than the number of particles at lower energy levels. Therefore, most low-threshold lasers usually have a four-level band structure. Pure two-dimensional (2D) and three-dimensional (3D) perovskites are single-phase materials, and their behavior is similar to a three-level laser system. In contrast, quasi-two-dimensional (quasi-2D) perovskites can be regarded as four-level systems with increased stability. However, the current quasi-two-dimensional perovskite is prone to uneven phase distribution, which leads to disordered states in space and energy, increases non-radiative recombination channels, reduces energy transfer efficiency, and makes it difficult to form a standard four-level structure state, which is not conducive to population inversion and the final laser emission. In addition, due to the soft lattice structure characteristics of perovskite, excited carriers (excitons) are prone to exciton-phonon coupling with lattice vibrations, which greatly affects the transmission of carriers and the final realization of stimulated radiation amplification. Summary of the invention
[0003] In view of the shortcomings of the prior art, the present application proposes a room temperature continuous wave perovskite laser based on chiral amine ligands and a preparation method thereof.
[0004] According to a first aspect of an embodiment of the present application, a room temperature continuous wave perovskite laser based on a chiral amine ligand is provided, comprising: An optical microcavity, a gain medium, and a spacer layer, wherein the gain medium is sandwiched between the optical microcavity and the spacer layer, and a reflective layer is plated on the spacer layer: The gain medium is a mixed material including a perovskite material, which is uniformly distributed in the optical microcavity in the form of a thin film with a thickness of 10 nm to 1 mm; The composition of the perovskite material is A'2A n-1 B n X 3n+1 , wherein A' is an organic chiral amine ion, A is a monovalent cation, B is a divalent metal cation, X is an anion, and n is a positive integer; A' is a combination of one or more of S / R-p-bromo-1-phenylethylamine s-Br-MBA, S-α-methylbenzylamine s-MBA, S / R-1-naphthylethylamine S / R-1-NEA, and S / R-2-aminobutane; A is a cesium ion Cs + , methylamine ion MA + , formamidinium ion FA + , ethylamine ion EA + , guanidine ion GA + 、Isopropylamine ion IPA + One or more combinations thereof; B is lead ion Pb 2+ 、Sn 2+ 、Ge 2+ 、Indium ion In 2+ 、Bi ion 2+ One or more combinations of; X is a chloride ion Cl - 、Br - 、Iodide ion I - A combination of one or more of .
[0005] Furthermore: the mixed material includes one or more of organic small molecule materials, organic polymer materials, inorganic oxide materials, III-V materials, II-VI materials, rare earth materials and perovskite materials, thereby reducing the defect density of perovskite.
[0006] Furthermore: the type of the optical microcavity is a distributed Bragg reflector (DBR), a distributed feedback Bragg grating (DFB), a photonic crystal (PC), a continuous bound state structure (BIC), a topological photonic crystal (TC) or a whispering gallery mode (WGM) microcavity, which enhances the interaction between light and matter and promotes laser emission.
[0007] According to a second aspect of an embodiment of the present application, a method for preparing a room temperature continuous wave perovskite laser based on a chiral amine ligand is provided, which is used to prepare the room temperature continuous wave perovskite laser based on a chiral amine ligand as described in the first aspect, and specifically comprises the following steps: preparing an optical microcavity as a bottom reflective layer; Prepare a gain medium: A'X, AX, and BX2 are placed in a solvent to obtain a perovskite precursor solution; spin-coat or drop-coat the perovskite precursor solution on the bottom reflective layer, anneal, and crystallize to obtain a gain medium; Spin coating the polymer on the gain medium to form a spacer layer; The layer is vacuumed and a top reflection layer is formed on the spacer layer by thermal evaporation.
[0008] Furthermore: on quartz, sapphire or flexible substrate polyethylene terephthalate (PET), a multilayer silicon dioxide / tantalum pentoxide dielectric layer is deposited by sputtering or electron beam evaporation to form a distributed Bragg reflector, i.e., a bottom reflection layer; the thickness of each dielectric film is λ / 4n, where λ is the central wavelength of light emission of the gain medium, and n is the refractive index of the dielectric layer material.
[0009] Furthermore: before the perovskite precursor solution is spin-coated or drop-coated on the bottom reflective layer, the bottom reflective layer is subjected to oxygen plasma etching treatment to enhance the hydrophilicity of the substrate surface, which is beneficial to the complete spreading of the solution and the subsequent spin coating process.
[0010] Furthermore: 0.5% mol molecular additives are also added to the perovskite precursor solution and filtered through a polytetrafluoroethylene hydrophobic filter membrane, wherein the solvent is any one or more of N,N-dimethylformamide DMF, dimethyl sulfoxide DMSO, γ-butyrolactone GBL, and dimethylacetamide DMA; the molecular additives are a mixture of one or more of polymers, small molecules, and oxides, and the polymer is a mixture of one or more of polymethyl methacrylate PMMA, polyethylene glycol PEG, polyethylene oxide PEO, and polyvinyl pyrrolidone PVP; the small molecules are a mixture of one or more of potassium bromide KBr, potassium thiocyanate KSCN, methyl ammonium chloride MACl, and phenethyl ammonium bromide; the oxide is a mixture of one or more of NiOx, ZnO, and SnO2 to reduce the defect density during the film formation process.
[0011] Furthermore: the molar ratio of A'X, AX, and BX2 is 2:1:1-2:3:4, and a thin film is formed by spin coating at a rotation speed of 2000-6000 rpm for 30-60s, which can form a uniform gain layer thin film with high crystallinity and low roughness.
[0012] Furthermore, when the polymer is spin-coated on the gain medium, the rotation speed is 2000-6000 rpm and the time is 30-60 s, which can form a uniform spacer layer film with high crystallinity and low roughness.
[0013] Further: vacuum treatment is performed to reduce the metal evaporation temperature. When the vacuum degree reaches 5×10 -5 Pa, metallic silver is evaporated on the spacer layer to form a top reflective layer with a reflectivity of >99%.
[0014] The technical solution provided by the embodiments of the present application may have the following beneficial effects: 1. This method uses a solution method and other low-cost methods to prepare high-quality quasi-two-dimensional perovskite films (i.e., gain media) based on chiral amine ligands, and uses chiral amine ligands to obtain highly ordered phase distribution, strong crystallization preferred orientation, and low lattice distortion. These characteristics enable the film to have: an excellent four-level material structure system, enhanced carrier pumping efficiency, and favorable population inversion; enhanced energy transfer efficiency from low two-dimensional phase (n=1) to high two-dimensional phase (n>5); increased number and strength of hydrogen bonds with the perovskite octahedral framework, effectively inhibiting the electroacoustic coupling effect, etc. The prepared perovskite film is combined with a high-quality optical microcavity, and its threshold is 1-3 orders of magnitude lower than that of traditional semiconductor lasers. The laser threshold is 1.57mW / cm under continuous light pumping. 2 , which is the lowest threshold in perovskite single-mode / multi-mode lasers at present; 2. The perovskite laser prepared by this method can be combined with various incoherent or coherent light sources (such as commercial III-V light-emitting diodes (LEDs), organic light-emitting diodes (OLEDs), quantum dot light-emitting diodes (QD-LEDs), perovskite light-emitting diodes (PeLEDs), micro-light-emitting diodes (micro-LEDs), laser diodes (LDs), tungsten-halogen lamps, etc.) to construct electrically pumped perovskite laser chips.
[0015] 3. The laser device prepared by this method has good temporal and spatial coherence and good polarization characteristics, and can be further used in low-threshold coherent light sources, slow light devices, quantum computing, optical computing, photonic chips, optoelectronic integration and other fields.
[0016] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0018] Figure 1 Schematic diagram of the mechanism of the quasi-two-dimensional perovskite laser based on chiral amine and non-chiral ligand prepared in Example 1; Figure 2 A schematic diagram showing the comparative characterization of the absorption and luminescence spectra and the luminescence quantum efficiency of the quasi-two-dimensional perovskite based on chiral amine and non-chiral ligand prepared in Example 1; Figure 3 Schematic diagram of stimulated emission amplification and threshold comparison characterization of the quasi-two-dimensional perovskite based on chiral amine and non-chiral ligand prepared in Example 1; Figure 4 A schematic diagram showing the comparative characterization of transient absorption spectra and energy transfer efficiency of the quasi-two-dimensional perovskite based on chiral amine and achiral ligand prepared in Example 1; Figure 5 Schematic diagram of the preparation of the quasi-two-dimensional perovskite continuous light laser based on chiral amine ligands prepared in Example 1 and the characterization of laser threshold and laser coherence; Figure 6 Schematic diagram of the comparative characterization of stimulated emission amplification of the quasi-two-dimensional perovskite based on chiral amine and non-chiral ligand prepared in Example 2; Figure 7 Schematic diagram of comparative characterization of stimulated emission amplification of quasi-two-dimensional perovskite based on chiral amine and non-chiral ligand prepared in Example 3; Figure 8 Schematic diagram of the comparative characterization of stimulated emission amplification of the quasi-two-dimensional perovskite based on chiral amine and non-chiral ligand prepared in Example 4. DETAILED DESCRIPTION
[0019] Here, exemplary embodiments are described in detail, and examples thereof are shown in the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The implementations described in the following exemplary embodiments do not represent all implementations consistent with the present application.
[0020] The terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application are also intended to include plural forms, unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used in this article refers to and includes any or all possible combinations of one or more associated listed items.
[0021] The present invention is further explained below in conjunction with the accompanying drawings.
[0022] Example 1
[0023] This embodiment introduces a method for preparing a room temperature continuous wave quasi-two-dimensional perovskite laser based on a chiral amine ligand, and the specific steps are as follows: Step 1: Place a 1.1 mm thick quartz glass substrate in an ultrasonic machine and wash it with deionized water and ethanol for 10 minutes. After washing and drying in a vacuum oven, place the glass substrate in a sample holder. Place the sample holder with the glass substrate in an electron beam coating machine and perform vacuum treatment. When the vacuum degree reaches 4×10 -4 Pa, SiO2 and Ta3O5 are sequentially evaporated on a quartz glass substrate, 7 groups of evaporation, the evaporation rate is controlled at 0.4nm / s, the thickness of each SiO2 layer is 63.21nm, the thickness of each Ta3O5 layer is 93.57nm, forming a DBR bottom reflection layer with high reflectivity (>98%).
[0024] Step 2: The dried DBR bottom reflective layer is treated with oxygen plasma etching for 8-15 minutes.
[0025] Step 3: Dissolve the material with a molar ratio of S-Br-MBABr / Rac-Br-MBABr: FABr: PbBr2 = 2:1:1 in a 1 mL DMF, DMSO mixed solvent to form a 0.5 mol L -1 The perovskite precursor solution, in which the ratio of DMF to DMSO is 1:4.
[0026] Step 4: After filtering 50 μL of the perovskite precursor solution through a polytetrafluoroethylene hydrophobic filter membrane, evenly drip it on the bottom reflective layer of the DBR; adjust the spin coating time of the coater to 60 s, control the spin coating speed to 5000 rpm / min, and drip chlorobenzene solution into the top hole at 45 s after starting spin coating; place the bottom reflective layer of the DBR spin-coated with the perovskite precursor solution on a hot stage for annealing at 100°C for 10 minutes to form a 100 nm thick perovskite light-emitting layer, i.e., a gain medium in the form of a perovskite film.
[0027] Step 5: Weigh 10-200 mg of PMMA powder and dissolve it in chlorobenzene or toluene solvent for later use.
[0028] Step 6: Spin-coat a PMMA optical microcavity spacer layer on the perovskite film to increase the cavity length. The PMMA solution concentration is 220 mg / ml, the spin-coating speed is 5000 rpm, and after spin-coating, heat on a hot stage at 120°C for 10 minutes for curing.
[0029] Step 7: Place the sample obtained in step 4 into a thermal evaporation coating machine and perform vacuum treatment. When the vacuum degree reaches 5×10 -5 Pa, metallic silver is evaporated on the sample with a thickness of 320nm to form a top reflective layer with a reflectivity of >99%. After the thermal evaporation is completed, the device is taken out of the evaporation chamber, and the laser preparation is completed.
[0030] Place the laser on an upright microscope platform, focus the continuous laser with a wavelength of 405nm onto the gain medium layer of the device through a 10X objective lens, and place a wheel-type attenuator in front of the laser to adjust the excitation intensity. Place a polarizer in front of the spectrometer detector, rotate the angle of the polarizer, and measure the polarization of the generated laser beam. The luminous beam of the quasi-two-dimensional laser based on chiral amine ligands is divided into two beams after passing through a beam splitter, one part of which continues to move forward through the beam splitter (reference arm), and the other part is reflected (signal arm). These two light beams reach the mirror on the other side through different paths, are reflected back again, and reunite through the beam splitter to measure the temporal and spatial coherence of the beam.
[0031] Figure 1This is a schematic diagram showing the mechanism comparison of stimulated emission amplification by preparing quasi-two-dimensional perovskite films based on chiral and achiral amine ligands. As can be seen from the schematic diagram, when the two-dimensional phase in the quasi-two-dimensional perovskite film is excited at an energy higher than the band gap, the excitons in the valence band absorb energy and transition to the conduction band, and the high-energy hot excitons gradually cool to the band edge energy level through scattering collisions and electroacoustic coupling. In addition, both quasi-two-dimensional perovskites prepared based on chiral and achiral amine ligands can form a four-level structure. However, compared with chiral amines, the quasi-two-dimensional perovskite film prepared by achiral amines can also form a four-level structure, but due to the smaller strength and number of hydrogen bonds between achiral amines and perovskite octahedra, the overall structural stability of the lattice is worse, and excited state carriers are prone to strong coupling with the lattice, resulting in lower energy transfer efficiency and difficulty in achieving population inversion. After excitation at an energy higher than the band gap, only fluorescence signals of radiation recombination can appear, and there is no stimulated emission amplification signal.
[0032] Figure 2 a in the figure is a schematic diagram of the quasi-two-dimensional film phase distribution. The n value distribution of the prepared perovskite film is n=1 and a three-dimensional phase. Figure 2 Figure b shows the absorption and fluorescence spectra of quasi-two-dimensional thin films based on chiral and achiral amines. The absorption spectra show that both have only two absorption peaks, n=1 and three-dimensional phase, indicating an orderly phase distribution. The fluorescence spectrum shows only the fluorescence emission peak of the three-dimensional phase, indicating effective energy transfer from the two-dimensional to the three-dimensional phase, but the fluorescence intensity of the chiral is stronger than that of the achiral, indicating a faster and more effective energy transfer mechanism, which is the key to achieving low-threshold stimulated emission amplification. Figure 2 Where c is the fluorescence quantum yield of the corresponding quasi-two-dimensional film. This result is consistent with the fluorescence spectrum, which also shows that the quasi-two-dimensional film based on chiral amines has higher energy transfer efficiency.
[0033] Figure 3 a and Figure 3 Figure b is the photoluminescence spectrum of the quasi-two-dimensional perovskite film prepared based on chiral and achiral amines as a function of pump energy. When the chiral amine-based film sample is excited by ultraviolet light, as the pump energy increases, the stimulated radiation amplification signal peak gradually appears, and then the achiral film is always a fluorescent signal, indicating that its threshold is very high or it is difficult to achieve particle number inversion and stimulated radiation amplification cannot occur. Figure 3 The c in is based on Figure 3 The diagram a in the figure shows the change of luminescence intensity and half-width with the change of pump energy. From the figure, it can be calculated that the stimulated emission amplification threshold of the chiral amine quasi-two-dimensional perovskite film is 7.95 μj / cm 2In order to further determine the energy transfer efficiency, we characterized the transient absorption spectra of the two thin film samples, extracted the n=1 exciton absorption peak and the carrier dynamics curve of the three-dimensional phase, and quantitatively calculated the energy transfer efficiency. Figure 4 a and Figure 4 b is the 2D spectrum of the tested transient absorption spectrum. It can be clearly seen that compared with the non-chiral amine-based sample, the absorption of the chiral amine-based two-dimensional film at the exciton peak rarely disappears, and the carrier energy is quickly transferred to the three-dimensional phase. Figure 4 From the calculation of c in , it can be obtained that the energy transfer efficiency of the chiral amine sample is 54%, and that of the achiral amine sample is 4.9%. The energy transfer efficiency is more than 10 times faster, which is conducive to the generation of stimulated radiation.
[0034] Based on the stimulated emission amplification achieved in the preparation of quasi-two-dimensional perovskite films with chiral amine ligands, we spin-coated the perovskite film on the bottom distributed Bragg reflector (DBR) mirror, then spin-coated PMMA on the perovskite film, and finally evaporated a silver mirror (320nm) on the top to prepare a vertical cavity surface emission (VCSEL) green laser ( Figure 5 The bottom DBRs consist of 7 pairs of alternating quarter-wavelength thick SiO2 / Ta2O5 dielectric layers to ensure high reflectivity (>98%). The bottom DBR reflector and the top silver mirror show high reflectivity (98.50% and 99.93%) at a wavelength of about 550 nm ( Figure 5 (b) As the thickness of the perovskite film is only about 100 nm, a polymethyl methacrylate (PMMA) spacer layer is added to increase the cavity length. Figure 5 The laser intensity and half-height width in c are characterized by the change of pump power density intensity. The calculated laser threshold is 1.57 W / cm 2 . Figure 5 The d in the figure shows that the laser peak width is 0.3 nm, and its quality factor is calculated to be 1800. Figure 5 e and Figure 5 As shown in f, the spatial coherence of the laser is further characterized using a Michelson interferometer. It can be clearly seen that clear coherent fringes appear above the threshold, indicating that the laser has good spatial coherence.
[0035] Example 2
[0036] This embodiment introduces a method for preparing a room temperature continuous wave quasi-two-dimensional perovskite laser based on a chiral amine ligand, and the specific steps are as follows: Step 1: Place a 1.1 mm thick quartz glass substrate in an ultrasonic machine and wash it with deionized water and ethanol for 10 minutes. After cleaning and wiping, place the dried glass substrate in a vacuum oven and place it in a sample holder. Place the sample holder with the glass substrate in an electron beam coating machine and perform vacuum treatment. When the vacuum degree reaches 4×10 -4 Pa, SiO2 and Ta3O5 are evaporated on the quartz glass substrate in sequence, 7 groups of evaporation, the evaporation rate is controlled at 0.4nm / s, the thickness of each SiO2 layer is 63.21nm, the thickness of each Ta3O5 layer is 93.57nm, forming a DBR bottom reflection layer with high reflectivity (>98%).
[0037] Step 2: The dried DBR bottom reflective layer is treated with oxygen plasma etching for 8-15 minutes.
[0038] Step 23: Dissolve the material with a molar ratio of S-MBABr / Rac-MBABr: FABr: PbBr2 = 2:1:1 in a 1 mL DMF, DMSO mixed solvent to form a 0.5 mol L -1 The perovskite precursor solution, in which the ratio of DMF to DMSO is 1:4.
[0039] Step 34: Filter 50 μL of the perovskite precursor solution through a polytetrafluoroethylene hydrophobic filter membrane, and evenly drip it on the bottom reflective layer of the DBR; adjust the spin coating time of the coater to 60 s, control the spin coating speed to 5000 rpm / min, and drip chlorobenzene solution into the top hole at 45 s after starting spin coating; place the bottom reflective layer of the DBR spin-coated with the perovskite precursor solution on a hot stage for annealing at 100°C for 10 minutes to form a 100 nm thick perovskite light-emitting layer, i.e., a gain medium in the form of a perovskite film.
[0040] Step 5: Weigh 10-200 mg of PMMA powder and dissolve it in chlorobenzene or toluene solvent for later use; Step 6: Spin-coat a PMMA optical microcavity spacer layer on the perovskite film to increase the cavity length. The PMMA solution concentration is 220 mg / ml, the spin-coating speed is 5000 rpm, and after spin-coating, heat on a hot stage at 120°C for 10 minutes for curing.
[0041] Step 57: Place the sample obtained in step 4 into a thermal evaporation coating machine and perform vacuum treatment. When the vacuum degree reaches 5×10 -5 Pa, metallic silver is evaporated on the sample with a thickness of 320nm to form a top reflective layer with a reflectivity of >99%. After the thermal evaporation is completed, the device is taken out of the evaporation chamber, and the laser preparation is completed.
[0042] The prepared device was placed on an upright microscope platform, and a femtosecond laser with a wavelength of 343nm was focused onto the gain medium layer of the device through a 10X objective lens. A wheel-type attenuator was placed in front of the laser to adjust the excitation intensity. A polarizer was placed in front of the spectrometer detector, and the angle of the polarizer was rotated to measure the polarization of the generated laser beam. Figure 6 a and Figure 6 Figure b is the photoluminescence spectrum of the quasi-two-dimensional perovskite film prepared based on chiral and achiral amines as a function of pump energy. When the chiral amine-based film sample is excited by ultraviolet light, as the pump energy increases, the stimulated radiation amplification signal peak gradually appears, and then the achiral film is always a fluorescent signal, indicating that its threshold is very high or it is difficult to achieve particle number inversion and stimulated radiation amplification cannot occur. Figure 6 The c in is based on Figure 6 The schematic diagram of the characterization of the change of luminescence intensity and half-height width as the pump energy changes is drawn in b. From the figure, it can be calculated that the stimulated emission amplification threshold of the chiral amine quasi-two-dimensional perovskite film is 10.87μj / cm 2 The law observed in this system is the same as that in Example 1, and other laser proof test steps are omitted, and Example 1 is mainly used for detailed description.
[0043] Example 3
[0044] This embodiment introduces a method for preparing a room temperature continuous wave quasi-two-dimensional perovskite laser based on a chiral amine ligand, and the specific steps are as follows: Step 1: Place a 1.1 mm thick quartz glass substrate in an ultrasonic machine and wash it with deionized water and ethanol for 10 minutes. After cleaning and wiping, place the dried glass substrate in a vacuum oven and place it in a sample holder. Place the sample holder with the glass substrate in an electron beam coating machine and perform vacuum treatment. When the vacuum degree reaches 4×10 -4 Pa, SiO2 and Ta3O5 are evaporated on the quartz glass substrate in sequence, 7 groups of evaporation, the evaporation rate is controlled at 0.4nm / s, the thickness of each SiO2 layer is 63.21nm, the thickness of each Ta3O5 layer is 93.57nm, forming a DBR bottom reflection layer with high reflectivity (>98%).
[0045] Step 2: The dried DBR bottom reflective layer is treated with oxygen plasma etching for 8-15 minutes.
[0046] Step 23: Dissolve the material with a molar ratio of S-2-BABr / Rac-2-BABr: FABr: PbBr2 = 2:1:1 in a 1 mL DMF, DMSO mixed solvent to form a 0.5 mol L -1The perovskite precursor solution, in which the ratio of DMF to DMSO is 1:4.
[0047] Step 34: Filter 50 μL of the perovskite precursor solution through a polytetrafluoroethylene hydrophobic filter membrane, and evenly drip it on the bottom reflective layer of the DBR; adjust the spin coating time of the coater to 60 s, control the spin coating speed to 5000 rpm / min, and drip chlorobenzene solution into the top hole at 45 s after starting spin coating; place the bottom reflective layer of the DBR spin-coated with the perovskite precursor solution on a hot stage for annealing at 100°C for 10 minutes to form a 100 nm thick perovskite light-emitting layer, i.e., a gain medium in the form of a perovskite film.
[0048] Step 5: Weigh 10-200 mg of PMMA powder and dissolve it in chlorobenzene or toluene solvent for later use; Step 6: Spin-coat a PMMA optical microcavity spacer layer on the perovskite film to increase the cavity length. The PMMA solution concentration is 220 mg / ml, the spin-coating speed is 5000 rpm, and after spin-coating, heat on a hot stage at 120°C for 10 minutes for curing.
[0049] Step 57: Place the sample obtained in step 4 into a thermal evaporation coating machine and perform vacuum treatment. When the vacuum degree reaches 5×10 -5 Pa, metallic silver is evaporated on the sample with a thickness of 320nm to form a top reflective layer with a reflectivity of >99%. After the thermal evaporation is completed, the device is taken out of the evaporation chamber, and the laser preparation is completed.
[0050] The prepared device was placed on an upright microscope platform, and a femtosecond laser with a wavelength of 343nm was focused onto the gain medium layer of the device through a 10X objective lens. A wheel-type attenuator was placed in front of the laser to adjust the excitation intensity. A polarizer was placed in front of the spectrometer detector, and the angle of the polarizer was rotated to measure the polarization of the generated laser beam. Figure 7 a and Figure 7 b in the figure is the photoluminescence spectrum of the quasi-two-dimensional perovskite film prepared based on chiral and non-chiral amines as the pump energy changes. Under the excitation of ultraviolet light, the stimulated emission amplification signal peak of the chiral amine-based film sample gradually appears as the pump energy increases, and then the non-chiral film is always a fluorescent signal, indicating that its threshold is very high or it is difficult to achieve population inversion and stimulated emission amplification cannot occur. The law observed in this system is the same as that in Example 1, and other laser proof test steps are omitted, and Example 1 is mainly used for detailed description.
[0051] Example 4
[0052] This embodiment introduces a method for preparing a room temperature continuous wave quasi-two-dimensional perovskite laser based on a chiral amine ligand, and the specific steps are as follows: Step 1: Place a 1.1 mm thick quartz glass substrate in an ultrasonic machine and wash it with deionized water and ethanol for 10 minutes. After cleaning and wiping, place the dried glass substrate in a vacuum oven and place it in a sample holder. Place the sample holder with the glass substrate in an electron beam coating machine and perform vacuum treatment. When the vacuum degree reaches 4×10 -4 Pa, SiO2 and Ta3O5 are evaporated on the quartz glass substrate in sequence, 7 groups of evaporation, the evaporation rate is controlled at 0.4nm / s, the thickness of each SiO2 layer is 63.21nm, the thickness of each Ta3O5 layer is 93.57nm, forming a DBR bottom reflection layer with high reflectivity (>98%).
[0053] Step 2: Dissolve S-1-NEABr / Rac-NMABr: FABr: PbBr2 in a 1 mL DMF / DMSO mixed solvent at a molar ratio of 2:1:1 to form a 0.5 mol L -1 The perovskite precursor solution, in which the ratio of DMF to DMSO is 1:4.
[0054] Step 3: Evenly drop 50 μL of perovskite precursor solution on the bottom reflective layer of the DBR; adjust the spin coating time of the coater to 60 s, control the spin coating speed to 5000 rpm / min, and drip chlorobenzene solution into the top hole at 45 s after starting spin coating; place the bottom reflective layer of the DBR spin-coated with the perovskite precursor solution on a hot stage for annealing at 100°C for 10 minutes to form a 100 nm thick perovskite light-emitting layer, i.e., a gain medium in the form of a perovskite film.
[0055] Step 4: Weigh 10-200 mg of PMMA powder and dissolve it in chlorobenzene or toluene solvent for later use; Step 5: Spin-coat a PMMA optical microcavity spacer layer on the perovskite film to increase the cavity length. The PMMA solution concentration is 220 mg / ml, the spin-coating speed is 5000 rpm, and after spin-coating, heat on a hot stage at 120°C for 10 minutes for curing.
[0056] Step 6: Place the sample obtained in step 4 into a thermal evaporation coating machine and perform vacuum treatment. When the vacuum degree reaches 5×10 -5 Pa, metallic silver is evaporated on the sample with a thickness of 320nm to form a top reflective layer with a reflectivity of >99%. After the thermal evaporation is completed, the device is taken out of the evaporation chamber, and the laser preparation is completed.
[0057] The prepared device was placed on an upright microscope platform, and a femtosecond laser with a wavelength of 343nm was focused onto the gain medium layer of the device through a 10X objective lens. A wheel-type attenuator was placed in front of the laser to adjust the excitation intensity. A polarizer was placed in front of the spectrometer detector, and the angle of the polarizer was rotated to measure the polarization of the generated laser beam. Figure 8 a and Figure 8 b in the figure is the photoluminescence spectrum of the quasi-two-dimensional perovskite film prepared based on chiral and non-chiral amines as the pump energy changes. Under the excitation of ultraviolet light, the stimulated emission amplification signal peak of the chiral amine-based film sample gradually appears as the pump energy increases, and then the non-chiral film is always a fluorescent signal, indicating that its threshold is very high or it is difficult to achieve population inversion and stimulated emission amplification cannot occur. The law observed in this system is the same as that in Example 1, and other laser proof test steps are omitted, and Example 1 is mainly used for detailed description.
[0058] Those skilled in the art will readily appreciate other embodiments of the present application after considering the specification and practicing the contents disclosed herein. The present application is intended to cover any variations, uses or adaptations of the present application, which follow the general principles of the present application and include common knowledge or customary technical means in the art that are not disclosed in the present application.
Claims
1. A room temperature continuous wave perovskite laser based on chiral amine ligands, comprising an optical microcavity, a gain medium, and a spacer layer, wherein the gain medium is sandwiched between the optical microcavity and the spacer layer, and a reflective layer is plated on the spacer layer, characterized in that: The gain medium is a mixed material including a perovskite material, which is uniformly distributed in the optical microcavity in the form of a thin film with a thickness of 10 nm to 1 mm; The composition of the perovskite material is A'2A n-1 B n X 3n+1 , wherein A' is an organic chiral amine ion, A is a monovalent cation, B is a divalent metal cation, X is an anion, and n is a positive integer; A' is a combination of one or more of S / R-p-bromo-1-phenylethylamine s-Br-MBA, S-α-methylbenzylamine s-MBA, S / R-1-naphthylethylamine S / R-1-NEA, and S / R-2-aminobutane; A is a cesium ion Cs + , methylamine ion MA + , formamidinium ion FA + , ethylamine ion EA + , guanidine ion GA + 、Isopropylamine ion IPA + One or more combinations thereof; B is lead ion Pb 2+ 、Sn 2+ 、Ge 2+ 、Indium ion In 2+ 、Bi ion 2+ One or more combinations of; X is a chloride ion Cl - 、Br - 、Iodide ion I - A combination of one or more of .
2. The room temperature continuous wave perovskite laser based on chiral amine ligands according to claim 1, characterized in that: The mixed material includes one or more of organic small molecule materials, organic polymer materials, inorganic oxide materials, III-V materials, II-VI materials, rare earth materials, and perovskite materials.
3. The room temperature continuous wave perovskite laser based on chiral amine ligands according to claim 1, characterized in that: The optical microcavity type is a distributed Bragg reflector, a distributed feedback Bragg grating, a photonic crystal, a continuous bound state structure, a topological photonic crystal or a whispering gallery mode.
4. A method for preparing a room temperature continuous wave perovskite laser based on a chiral amine ligand, characterized in that: For preparing a room temperature continuous wave perovskite laser based on a chiral amine ligand as claimed in any one of claims 1 to 3, the method specifically comprises the following steps: preparing an optical microcavity as a bottom reflective layer; Prepare a gain medium: A'X, AX, and BX2 are placed in a solvent to obtain a perovskite precursor solution; spin-coat or drop-coat the perovskite precursor solution on a bottom reflective layer, anneal, and crystallize to obtain a gain medium; Spin coating the polymer on the gain medium to form a spacer layer; The layer is vacuumed and a top reflection layer is formed on the spacer layer by thermal evaporation.
5. The method for preparing a room temperature continuous wave perovskite laser based on a chiral amine ligand according to claim 4, characterized in that: On quartz, sapphire or flexible substrate polyethylene terephthalate, a multilayer silicon dioxide / tantalum pentoxide dielectric layer is deposited by sputtering or electron beam evaporation to form a distributed Bragg reflector, i.e., a bottom reflection layer; the thickness of each dielectric film is λ / 4n, where λ is the central wavelength of the gain medium light emission and n is the refractive index of the dielectric layer material.
6. The method for preparing a room temperature continuous wave perovskite laser based on a chiral amine ligand according to claim 4, characterized in that: Before the perovskite precursor solution is spin-coated or drop-coated on the bottom reflective layer, the bottom reflective layer is subjected to oxygen plasma etching treatment.
7. The method for preparing a room temperature continuous wave perovskite laser based on a chiral amine ligand according to claim 4, characterized in that: 0.5 mol% molecular additives are also added to the perovskite precursor solution, and filtered through a polytetrafluoroethylene hydrophobic filter membrane, wherein the solvent is a mixture of any one or more of N,N-dimethylformamide, dimethyl sulfoxide, γ-butyrolactone, and dimethylacetamide; and the molecular additives are a mixture of one or more of polymers, small molecules, and oxides.
8. The method for preparing a room temperature continuous wave perovskite laser based on a chiral amine ligand according to claim 4, characterized in that: The molar ratio of A'X, AX and BX2 is 2:1:1-2:3:
4.
9. The method for preparing a room temperature continuous wave perovskite laser based on a chiral amine ligand according to claim 4, characterized in that: When the polymer is spin-coated on the gain medium, the rotation speed is 2000-6000 rpm and the time is 30-60 s.
10. The method for preparing a room temperature continuous wave perovskite laser based on a chiral amine ligand according to claim 4, characterized in that: Vacuum treatment was performed. When the vacuum degree reached 5×10 -5 Pa, metallic silver is evaporated on the spacer layer as the top reflective layer.
Citation Information
Patent Citations
Polarization output conversion device on basis of long-wavelength rotating VCSEL (vertical cavity surface emitting lasers)
CN106785897A
Device for injecting spin-polarised charge carriers and for reflecting light
CN111819745A
Perovskite gain medium, preparation method thereof and application of perovskite gain medium in continuous optical pump laser at room temperature
CN114530753A
Depth reserve pool calculation system and method based on spinning vertical cavity surface emitting laser
CN115145535A
Green perovskite laser and preparation method thereof
CN116742473A
Cited By
Electrically-driven perovskite laser and preparation method thereof
CN121055157A